Money's eyes: the visual preparation of financial markets. - Pryke, Michael (Economy & Society, 2010)
A study examined the implications of using visualization software to enable better visual imagination of and interaction with markets as they unfold in real time. Data were obtained from interviews with those engaged in developing and using the latest in visualization software. Findings indicated that the latest visual turn within finance should be given a more central position in contemporary financial market research. Findings are discussed in detail.